2023
DOI: 10.1371/journal.pntd.0011119
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted serum metabolomics analysis of Trichinella spiralis-infected mouse

Abstract: Background Trichinellosis, caused by a parasitic nematode of the genus Trichinella, is a zoonosis that affects people worldwide. After ingesting raw meat containing Trichinella spp. larvae, patients show signs of myalgia, headaches, and facial and periorbital edema, and severe cases may die from myocarditis and heart failure. The molecular mechanisms of trichinellosis are unclear, and the sensitivity of the diagnostic methods used for this disease are unsatisfactory. Metabolomics is an excellent tool for study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…According to our previous study, ( Chienwichai et al., 2023 ) the metabolomics analysis of T. spiralis -infected mouse sera has been reported. We found that D-glucose 6-phosphat found in adult worms and larvae was also detected in the T. spiralis -infected mouse sera at 4 weeks post-infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to our previous study, ( Chienwichai et al., 2023 ) the metabolomics analysis of T. spiralis -infected mouse sera has been reported. We found that D-glucose 6-phosphat found in adult worms and larvae was also detected in the T. spiralis -infected mouse sera at 4 weeks post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome extraction was performed, according to the previous study ( Chienwichai et al., 2023 ). For ES product, 20 µL of solution was mixed with 80 µL of cold methanol using vortex for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations